PENERAPAN AKUNTANSI LINGKUNGAN UNTUK MENGOPTIMALKAN TANGGUNG JAWAB INDUSTRI GULA - Susiana Sari; Nengah Sudjana; Devi Farah Azizah (Jurnal Administrasi Bisnis, 2013)
Environmental accounting is used to identify hidden costs and improve industrial performance in the field of environmental management. The identification of costs is done by assessing the activities and benefits of environmental management from cost standpoint. The existence of environmental accounting is also used as a management and information tool to stakeholders regarding environmental performance in optimizing social responsibility. The research was conducted at Pabrik Gula Lestari in Ngrombot Nganjuk. This study aims to identify and explain the environmental accounting and environmental activities in order optimizing social responsibility at Pabrik Gula Lestari. Type of research is descriptive research by qualitative approach. The data sources used are interviews with key informants, observation and documentation. Based on the analysis indicates that the Pabrik Gula Lestari has implemented environmental accounting but the reforestation cost was budgeted at cost of donations. The analysis also revealed that Installation Management Wastewater Treatment Plant (WWTP) and bowler machines need additional maintenance costs to minimize the pollution so it does not interfere with public health. If Pabrik Gula Lestari wants to improve the quality of the environment for social responsibility, Pabrik Gula Lestari should optimize equipment maintenance and provide for public health programs. Keyword : Cost Accounting, Accounting Environmental, Corporate Social Responsibility